Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1182/blood-2020-138911
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Transfusion Transmissible Infections in Beta-Thalassemia Major Patients of Pakistan: A Systematic Review

Abstract: Introduction: β-thalassemia major (TM) is one of the most prevalent inherited hemoglobinopathies in Pakistan. It has one of the highest prevalence of transfusion-dependent TM patients globally, with an estimated greater than 100,000 active cases. Each year, an estimated 5000-9000 new cases of TM are being diagnosed in the country. Blood transfusions (BT) are essential in the management of severe TM; it is critical to have a safe BT to reduce the risk of transfusion transmissible infections (TTIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Showed similar results for the prevalence of hepatitis virus among thalassemia patients in a global countries such as in Pakistan 3.13% [11]. and 3.69% in West Bengal [12].…”
Section: Discussionmentioning
confidence: 56%
“…Showed similar results for the prevalence of hepatitis virus among thalassemia patients in a global countries such as in Pakistan 3.13% [11]. and 3.69% in West Bengal [12].…”
Section: Discussionmentioning
confidence: 56%
“…An even lower prevalence of co-infections with HIV, HBV and syphilis has been reported in other regions 7 , 8 , 9 …”
Section: Discussionmentioning
confidence: 83%
“…This is likely plausible as age is a proxy measure of time available for an individual to be exposed to potential risk factors. Studies in Pakistan and India 8 , 9 have also found older age to be related to increased HCV risk among persons who regularly receive blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infection is the most prevalent transfusion transmissible infections in thalassemia following infection with hepatitis B virus (HBV) and an increased risk of contracting the human immunodeficiency virus (HIV). 17…”
Section: Infectionmentioning
confidence: 99%